The use of family group conferences in mental health: Barriers for implementation - Schout, Gert; van Dijk, Marjolein; Meijer, Ellen; Landeweer, Elleke; de Jong, Gideon (Journal of social work : JSW, 2017)
Summary The number of compulsory admissions in Dutch psychiatry has increased in the past 25 years. The reduction of coercion with Family Group Conferences in youth care has been successful. How, when and under what conditions can Family Group Conferences reduce coercion in adult psychiatry, is subject of an extensive inquiry. This paper, however, focusses on the reverse question, namely, in what circumstances can Family Group Conferences not be deployed? An answer to this question provides insights regarding situations in which Family Group Conferences may (not) be useful. Barriers in 17 cases were examined using multiple case studies. Findings The following barriers emerged: (1) the acute danger in coercion situations, the limited time available, the fear of liability and the culture of control and risk aversion in mental health care; (2) the severity of the mental state of clients leading to difficulties in decision-making and communication; (3) considering an Family Group Conference and involving familial networks as an added value in crisis situation is not part of the thinking and acting of professionals in mental health care; (4) clients and their network (who) are not open to an Family Group Conference. Applications Awareness of the barriers for Family Group Conferences can help to keep an open mind for its capacity to strengthen the partnership between clients, familial networks and professionals. The application of Family Group Conferences can help to effectuate professional and ethical values of social workers in their quest for the least coercive care.